Journalism and technological change historical perspectives, contemporary trends (Frankfurt Campus Verlag, 2014)
"This volume not only considers the implementation--the successes and failures--of new media technologies, but also the influence these technologies have had both on the practical demands and internal processes of media companies and on the professional roles, social positions, and self-perceptions of journalists. A thorough, interdisciplinary synthesis covering more than one hundred and fifty years of media in Europe and the United States"--From distributor's website.
"This volume is based on a conference that took place on 22.-23. März 2013 at Villa Lessing in Saarbrücken, organized by the Chair of Cultural and Media History at Saarland University"--Preface (page 7).
Includes bibliographical references and index.
Keywords: Journalism -- Technological innovations -- Congresses; Journalism -- History -- Congresses; Online journalism -- Congresses